The Night the Epic Poem Died: Ends of Poetry in Giuseppe Parini’s La Notte - Dule, Griseldo (Quaderni d'Italianistica, 2022)
During the eighteenth century, the Italian peninsula witnessed many cultural changes coming from abroad, among which figured a new way of conceptualizing and experiencing the night. The dissemination of Enlightened ideas accelerated societal changes and solicited new literary endeavors. As the neoclassical season was burgeoning, there was an absence in the literary canon of acclaimed and national epic poems, a once-prestigious genre that elsewhere in Europe had already been replaced by the novel. This essay focuses on Il Vespro and La Notte, the last two unfinished sections of Il Giorno, Giuseppe Parini’s epic and satirical poem, and investigates the ways in which the Milanese poet analyzes the changes in his representation of the night. Through textual and thematic analysis, the essay underlines the original aspects of Parini’s antiphrastic depiction of the night.